Wyoming wilderness survival - Nelson, Jill Elizabeth (Love inspired suspense., 2025)
"Seeking refuge in the mountains... with killers in pursuit. Just as EMT Tracey Graham's murder conviction is about to be overturned, she is ambushed by the crime family who framed her -- and now want her dead. Fleeing into the woods sends her into the path of ex-cop Callum Mitchell, who has his own history with her assailants. But when his secluded cabin comes under attack, the wilderness is their only escape route. With Callum's toddler son in tow, they must evade hitmen while navigating treacherous terrain. But can they make it out alive...when there are predators around every corner?" --